KURS RUPIAH SEBAGAI MODERASI DARI PENGARUH CURRENT RATIO (CR), RETURN ON EQUITY (ROE), DEBT EQUITY RATIO (DER) TERHADAP HARGA SAHAM - Huda, Koirul; Faisol, Faisol; Winarko, Sigit Puji (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research aims to analyze the effect of CR, ROE and DER on stock prices with the rupiah exchange rate as a moderating variable. The sampling method used is purposive sampling. The sample used is 19 food and beverage industries listed on the IDX in 2019-2021. The data analysis technique used is Panel Data Regression Analysis using STATA 16. The results of the analysis show that ROE has a significant effect on stock prices but CR and DER have no significant effect to stock prices. The results of the analysis also show that the rupiah exchange rate can moderate the effect of ROE on stock prices. However, the rupiah exchange rate cannot moderate the effect of CR and DER on stock prices.